Validation study of the emotional empathy questionnaire for children - Flores Galaz, Mirta Margarita (Consorcio de Universidades Mexicanas A.C., 2017)
The objective of the study was to analyze the psychometric properties and validity of the Questionnaire Measure of Emotional Emphathy Mehrabian & Epstein, Spanish version of Garaigordobil. A total of 530 children were selected through non-probabilistic sampling, 262 (49.4%) boys and 268 (50.6%) girls, with a mean age of 10.81 years old (SD = 1.12) from public schoolsin Merida, Yucatan. Confirmatory factorial analysis revealed a good fit with two factors: empathy and non-empathy (χ2 (118) = 281.54, p < .001; CFI = 0.921, GFI = 0.942, AGFI = 0.925, TLI = 0.899, RMSEA = .051, The replicability of the original model of Mehrabian and Epstein and of the validated version with Spanish children Garaigordobil, was confirmed, and the results showed high scores in empathy, being the girls who showed higher levels of empathy than the boys. Similar findings were produced in these Mexican children.